PENGARUH UKURAN AUDITOR, AUDITOR SPESIALISASI INDUSTRI DAN INDEPENDENSI AUDITOR TERHADAP PRAKTIK MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEX TAHUN 2010-2012) - Salman Ali; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2014)
Earnings management rise as a direct consequence from the manager or preparers of financial statements to management accounting information efforts, especially, for the personal and / or company benefits. Earnings management occurs when managers use judgmen in financial reporting and transaction regulations to alter financial reports to mislead some stakeholders about the company's key financial performance, or to influence contractual outcomes that depend on reported accounting numbers.This research aimed to analyze the effect of auditor size, auditor industry specialization and auditor independence on earnings management using control variables, namely firm size , growth prospects, operating cash flow and leverage. This research use a company listed on the Indonesia Stock Exchange and incorporated in the Jakarta Islamic Index ( JII ) during 2010-2012 as samples, which is in accordance with the criteria established and acquired as many as 14 companies. This research uses multiple regression analysis test to determine the auditor size effect, auditor industry specialization and auditor independence on earnings management. Auditor size result reveals positive and significants effect on earnings management, while the auditor industry specialization and auditor independence has no significant effect on earnings management. In control variables test, only the operating cash flows affect earnings management, While the company size, growth prospects and leverage does not affect the earnings management.